Dynamically adaptive soft metamaterial for wearable human–machine interfaces - Ugur Tanriverdi; Guglielmo Senesi; Tarek Asfour; Hasan Kurt; Sabrina L. Smith; Diana Toderita; Joseph Shalhoub; Laura Burgess; Anthony M. J. Bull; Firat Güder (Nature Communications)
Abstract Our bodies continuously change their shape. Wearable devices made of hard materials, such as prosthetic limbs worn by millions of amputees every day, cannot adapt to fluctuations in the shape and volume of the body caused by daily activities, weight gain or muscle atrophy. We report a meta-material (Roliner) that is a dynamically adaptive human-machine interface for wearable devices. In this work, we focus on prosthetic limbs as the first application of Roliner. Roliner is made of silicone elastomers with embedded millifluidic channels that can be pneumatically pressurized. Roliner can reconfigure its material properties (behave like silicone or polyurethane with different shore hardness in different areas and times) and volume/shape based on the preference of the amputee in real-time, acting as a spatiotemporally adaptive meta-material. Preclinical studies of Roliner have demonstrated non-inferiority in operation and improved comfort for amputees.